Regionálně metodický pohled na současnou problematiku rozvoje společnosti - Mandysová, Ivana (Univerzita Pardubice, 2000)
Since 1989 there has been in Czech Republic renaissance of theoretical and empirical work on the regional politics. Using new tools - in particular, methods of analysis as stated in the article below, has emerged as one of the most exicting areas of contemporary methodology of regional econoomics.
Keywords: regiony; rozvoj společnosti; vývoj